ANALISIS PENGARUH DIVERSIFIKASI PERUSAHAAN TERHADAP TINGKAT KOMPENSASI CEO, STRUKTUR KEPEMILIKAN DIREKSI, DAN KOMPOSISIDEWAN KOMISARIS - , Maria Jessica Diaz Viera ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to provide empirical evidence that there is a difference on CEO compensation, director ownership structure, and fraction of board of commissioner between diversified and focus firms. Furthermore, this study also aims to prove that diversification effects the CEO compensation, director ownership structure, and fraction of board of commissioner. Independent variables used in this study are dummy variable for diversified firm, firmâs performance, firmâs size, firmâs debt, firmâs growth, and CEO tenure. Dependent variables used in this study are CEO compensation, director ownership structure, and fraction of board of commissioner. The samples in this study are all non-financial firms that listed in Indeks Kompas 100 from 2009 to 2011. This research use Wilcoxon Sign Rank Test, Mann Whitney, Independent Sample T- Test and Multiple Linear Regression to analyze the data. The results of this study prove that there is no difference on CEO compensation, director ownership structure, and fraction of board of commissioner between diversified and focus firms. Result from Multiple Linear Regression also provide an evidence that diversification does not affect the CEO compensation, director ownership structure, and fraction of board of commissioner.